MANAGERIAL STRESS IN THE PROCESS OF DIGITAL TRANSFORMATION OF ORGANIZATION - Radnović Vukčević, Jelena; Radnović, Vladana; Nićin, Slobodan; Prodanović, Branislava (Poslovna ekonomija, 2024)
Digital transformation is an essential process in modern business that enables organizations to fundamentally redefine their operations, communication, and business models through the integration of digital technologies. This process represents more than a mere technical upgrade; it is a profound change that requires the inclusion of technology in the foundation of daily activities in order to improve efficiency, innovation, and competitiveness in the market. In the context of globalization, rapid adaptation to digital trends becomes crucial for preserving market position, and successful implementation of digital transformations can result in significant savings, resource optimization, and productivity improvements. Digitization also enables a better understanding of customer needs through the analysis of large amounts of data, contributing to the creation of personalized products and services. However, digital transformation also brings challenges, including managing organizational change, managerial stress due to rapid decision-making, continuous learning, and the need to adapt to new technologies. As a general phenomenon and an eminent factor of business activities, managerial stress manifests in different ways across the wide range of actions in the process of digital transformation of organizations. Human resource management is important in managing stress in the process of digital transformation of organizations, directing it into optimal frameworks where it manifests a positive dimension, aimed at enhancing the success of both individual business activities and overall results in the process of digital transformation of organizations.